Bile duct antibodies crossreacting with blood group antigens in primary sclerosing cholangitis. Issue 6 (June 1990) - Jeffrey, G P; Swanson, N R; Yarred, L J; Reed, W D
Abstract : Indirect immunoperoxidase histochemistry was used to localise and determine the disease, species, and tissue specificity of bile duct antibodies in primary sclerosing cholangitis. Serum was collected from: 29 patients with primary sclerosing cholangitis, 18 patients with ulcerative colitis alone, 19 patients with extrahepatic biliary obstruction of other causes, and 42 healthy control subjects. Bile duct antibodies reacted with an antigen localised to the small and large intrahepatic bile ducts. When blood group A human liver was used they were detected in 34% of patients with primary sclerosing cholangitis. They were not detected when blood group O human liver was used. Bile duct antibodies that reacted with obstructed and normal rabbit liver were detected in 34% and 17% respectively of patients with primary sclerosing cholangitis but were also present in similar proportions of control subjects. Colon antibodies that reacted with human and rabbit colon were found in 52% and 24% respectively of patients with primary sclerosing cholangitis. Absorption studies using blood group substances A and B abolished the reactivity of bile duct antibodies with human and rabbit liver and that of colon antibodies' with rabbit colon. Colon antibodies that reacted with human colon were not absorbed. Absorption studies using isolated peripheral white blood cells did not affect reactivity of bile duct or colon antibodies. We conclude that bile duct antibodies are disease, species, and tissue non-specific and react with blood group A/B antigens present in human and rabbit bile ducts and rabbit colon. This suggests that they do not play a role in the pathogenesis of primary sclerosing cholangitis.